2012
DOI: 10.1093/beheco/ars059
|View full text |Cite
|
Sign up to set email alerts
|

Boldness behavior and stress physiology in a novel urban environment suggest rapid correlated evolutionary adaptation

Abstract: Novel or changing environments expose animals to diverse stressors that likely require coordinated hormonal and behavioral adaptations. Predicted adaptations to urban environments include attenuated physiological responses to stressors and bolder exploratory behaviors, but few studies to date have evaluated the impact of urban life on codivergence of these hormonal and behavioral traits in natural systems. Here, we demonstrate rapid adaptive shifts in both stress physiology and correlated boldness behaviors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
234
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 310 publications
(256 citation statements)
references
References 64 publications
14
234
2
6
Order By: Relevance
“…We compared circulating corticosterone and gonadal GR and MR transcript abundance in sedentary urban and migrant juncos in our common garden study. Both in the field and a common garden, sedentary urban juncos, and migrant juncos that breed close-by had similar baseline levels of corticosterone during the breeding season (Atwell et al, 2012). Similar to these observations, our data collected during the period preceding the breeding season found no differences in baseline levels of corticosterone; sedentary urban and migrant juncos had similar levels of corticosterone over our 4-week captive study in early spring ( Figure 5A).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We compared circulating corticosterone and gonadal GR and MR transcript abundance in sedentary urban and migrant juncos in our common garden study. Both in the field and a common garden, sedentary urban juncos, and migrant juncos that breed close-by had similar baseline levels of corticosterone during the breeding season (Atwell et al, 2012). Similar to these observations, our data collected during the period preceding the breeding season found no differences in baseline levels of corticosterone; sedentary urban and migrant juncos had similar levels of corticosterone over our 4-week captive study in early spring ( Figure 5A).…”
Section: Discussionsupporting
confidence: 82%
“…A previous study (Atwell et al, 2012) conducted during the breeding season, found higher stress-induced corticosterone in a nearby rural breeding population compared to breeders from the urban San Diego population. We did not measure stress-induced corticosterone in this study, so we cannot say whether differences in stress-induced corticosterone levels might have delayed reproductive development in migrant juncos in San Diego.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…2009; Atwell et al. 2012). These responses to the urban environment are mediated by the organism's endocrine system (Bonier 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2011; Atwell et al. 2012). However, changes in endocrine patterns due to urban influences in general were not consistent between species, sexes, and life‐history stages (Bonier 2012).…”
Section: Introductionmentioning
confidence: 99%